Belonging to the West: Geopolitical Myths and Identity in Modern Greece - Nestoras, Antonios, author.
1 online resource (266 pages)
Keywords: Uncover the fascinating story of Greece's unwavering quest for European belonging. This thought-provoking book explores the intersection of geopolitics and political myth, tracing Greece's enduring determination to align with Europe and the West. From the early days of European integration to the challenges of the Eurocrisis, Greece's commitment remains steadfast. By analyzing the geopolitical myths that shape its identity, the book illuminates the multifaceted factors driving Greece's pro-European strategy and foreign policy. By introducing and using Analytical Geopolitics as a pioneering approach, the book provides a historical-structural framework and expands the role of myth in understanding international relations.